Institutionalization of Legal Institutions as a Theoretical and Methodological Basis for the Study of Legal Clinics - Mudrak , Roman (Actual problems of law (Aktual’ni problemi pravoznavstva), 2026)
The article provides a comprehensive theoretical and methodological analysis of approaches to understanding the institutionalization of legal institutions in contemporary legal science. It is substantiated that institutionalization should be considered as a complex multi-level process that includes the formation, legal formalization, organizational structuring, and functional stabilization of socially significant legal practices. The main scientific approaches to the interpretation of institutionalization are identified, including normative, socio-legal, and comprehensive (institutional) approaches, and their heuristic potential for the study of modern legal phenomena is examined. The research methodology is based on a complex combination of several methods. The comparative method is used to study the use of legal terminology, a doctrinal analysis of modern scientific literature is carried out, and individual legislative provisions are studied using the analysis and synthesis method. The study demonstrates the limitations of the purely normative approach, which fails to take into account the social nature of legal institutions, and justifies the need for a comprehensive approach that integrates normative, organizational, and functional dimensions. Particular attention is paid to the relationship between formal and informal components of institutionalization, which significantly influence the effectiveness of legal institutions in practice. It is argued that the level of institutionalization depends not only on the existence of legal regulation, but also on the degree of social recognition, stability of practices, and integration into the legal system. The applicability of these theoretical approaches to the study of legal clinics as a specific type of legal institution operating at the intersection of legal and educational systems is substantiated. It is concluded that the use of a comprehensive methodological framework provides a solid basis for further comparative legal analysis of the institutionalization of legal clinics.